2001
DOI: 10.1073/pnas.161292398
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesia, anxiety, and decreased hypoxic neuroprotection in mice lacking the adenosine A1receptor

Abstract: Caffeine is believed to act by blocking adenosine A1 and A2A receptors (A1R, A2AR), indicating that some A1 receptors are tonically activated. We generated mice with a targeted disruption of the second coding exon of the A1R (A1R ؊/؊ ). These animals bred and gained weight normally and had a normal heart rate, blood pressure, and body temperature. In most behavioral tests they were similar to A1R ؉/؉ mice, but A1R ؊/؊ mice showed signs of increased anxiety. Electrophysiological recordings from hippocampal slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
396
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 469 publications
(433 citation statements)
references
References 30 publications
32
396
3
2
Order By: Relevance
“…We found that elimination of A 1 Rs clearly affected synaptic physiology in hippocampus, confirming earlier results (Johansson et al, 2001;Masino et al, 2002). As noted previously, hippocampal slices from A 1 R −/− mice were insensitive to the application of exogenous adenosine.…”
Section: Slice Experimentssupporting
confidence: 92%
See 2 more Smart Citations
“…We found that elimination of A 1 Rs clearly affected synaptic physiology in hippocampus, confirming earlier results (Johansson et al, 2001;Masino et al, 2002). As noted previously, hippocampal slices from A 1 R −/− mice were insensitive to the application of exogenous adenosine.…”
Section: Slice Experimentssupporting
confidence: 92%
“…This adenosine application assessed functionally the genotype of each animal and in each case confirmed the genotype determined by PCR analysis. Previous studies demonstrated that adenosine has no effect on synaptic transmission in hippocampal slices from A 1 R −/− animals, has an intermediate effect in slices A 1 R +/− animals (due to the increased EC 50 for adenosine), and has the expected profound inhibitory effect in slices from A 1 R +/+ animals (Johansson et al, 2001;Masino et al, 2002).…”
Section: Electrophysiologymentioning
confidence: 96%
See 1 more Smart Citation
“…Animals were kept in a 12-hour light/dark cycle with lights on from 7 am to 7 pm in individually ventilated isolator cages and food and water were supplied ad libitum. Four different genotypes of mice were used in this study, all maintained on a C57BL/6 background: (1) wild type; (2) homozygous Adk-tg mice with brain wide overexpression of a conditional Adk-transgene, but lack of the endogenous Adk gene; these animals are characterized by high ADK expression in CA3 neurons and have been characterized previously (Fedele et al, 2005;Pignataro et al, 2007;Wu and Boison, 2007;Yee et al, 2007;Li et al, 2008); (3) fb-Adk-def mice with reduced levels of forebrain ADK were created based on Emx1-Cre driven recombination of the loxP-flanked Adk-transgene in Adk-tg mice (Li et al, 2008); (4) homozygous and heterozygous A 1 receptor knockout mice (Johansson et al, 2001;Fedele et al, 2006).…”
Section: Animalsmentioning
confidence: 99%
“…To investigate the possibility for spontaneous seizures in Adk-tg mice, 6 naïve animals were equipped with bipolar recording electrodes implanted into the CA3 region. In parallel, untreated homozygous and heterozygous A 1 receptor knockout mice (Johansson et al, 2001), as well as KA injected wild type mice 3 weeks after SE received intra-CA3 recording electrodes (n = 5 per group). One day after electrode implantation each animal was subjected to 8 hours of continuous EEG recordings.…”
Section: Spontaneous Seizures In Adk Overexpressing Transgenic Micementioning
confidence: 99%